DYNAMICS OF SST2 AND NT-PROBNP IN PATIENTS WITH ARTERIAL HYPERTENSION AND TYPE 2 DIABETES MELLITUS BASED ON COMBINED THERAPY WITH EPLERENONE AND TRIMETASIDINE ADDITION - Bilovol, O.M.; Kniazkova, I.I.; Kirienko, O.M.; Kuzminova, N.V.; Sushetska, A.S.; Starenkiy, V.P.; Abramova, L.P. (World of Medicine and Biology, 2023)
The purpose of our study was to investigate the effect of complex therapy with the addition of eplerenone and trimetazidine on the state of left ventricular diastolic function, as well as levels of soluble growth-stimulatingreceptor expressed by gene 2 and N-terminal fragment of brain natriuretic propeptide in patients with arterial hypertension with type 2 diabetes mellitus. After registration baseline data were recorded, 42 patients (group 1) were prescribed baseline therapy and 38 patients (group 2) were prescribed eplerenone 25-50 mg once daily and trimetazidine 80 mg once daily in addition to antihypertensive therapy for 3 months. The control group consisted of 20 practically healthy individuals. After the treatment, a significant decrease in the level of soluble growth-stimulatingreceptor expressed by gene 2 in the blood of patients in both groups was found, but in group 2 this indicator did not differ from the control group, while in group 1 it remained significantly higher than in healthy individuals. At the same time, the level of N-terminal fragment of brain natriuretic propeptide significantly decreased by 1.3 times and 1.6 times in groups 1 and 2, respectively, but remained significantly higher than in the control group. A significant decrease E/e`mean was determined in both groups of patients, but in group 2 by 8.9 % less than in group 2 and a decrease in the geometric parameters of the left atrium, more pronounced in group 2. Thus, the addition of eplerenone and trimetazidine to the complex therapy of patients with arterial hypertension and type 2 diabetes mellitus during 3 months improved diastolic function, and also had a positive effect on the biomarker of myocardial stress and fibrosis soluble growth-stimulatingreceptor expressed by gene 2 level and myocardial dysfunction N-terminal fragment of brain natriuretic propeptide concentration in serum
Keywords: soluble growth-stimulatingreceptor expressed by gene 2; N-terminal fragment of brain natriuretic propeptide; diastolic function; arterial hypertension; type 2 diabetes mellitus; eplerenone; trimetazidine